UNHCR's Political Role in Addressing Ethnic Rohingya in Medan - Rosintha Regina Manalu (International Journal on Social Science, Economics and Art, 2020)
This study tries to explain how the political role of UNHCR in addressing the Rohingya refugees. UNHCR is one of the international organizations engaged in the evacuation. Researchers try to explain how an international organization UNHCR to play its role as a political actor in carrying out the mandate given by the UN (United Nations). UNHCR in Indonesia, especially in Medan in running their political role is not alone, but in collaboration with various stakeholders, including IOM (International Organitation for Migration), Immigration, Government of Indonesia and other parties. This research is very interesting considering the issue of Rohingya refugees are talking about around the world. The problem in this research are researchers trying to see more detail how exactly the UNHCR as a political actor performing their duties. Does UNHCR has done its job well? How the processes undertaken by UNHCR in handling the Rohingya refugees? Already in accordance with the procedure or not the steps undertaken by UNHCR in its handling? This study is expected to answer questions about what role and how UNHCR's performance in handling the Rohingya refugees in Medan. In this research using descriptive qualitative method. Where the author will analyze the data obtained either from source books, magazines, legal documents, website pages and use the key informant interview techniques. The concept according to K.J Holsti in describing the role of politics and the use of methods of political analysis by Hudson used in this study.